2011
DOI: 10.1371/journal.pone.0025507
|View full text |Cite
|
Sign up to set email alerts
|

EGFR-Targeted Hybrid Plasmonic Magnetic Nanoparticles Synergistically Induce Autophagy and Apoptosis in Non-Small Cell Lung Cancer Cells

Abstract: BackgroundThe epidermal growth factor receptor (EGFR) is overexpressed in 80% of non-small cell lung cancer (NSCLC) and is associated with poor survival. In recent years, EGFR-targeted inhibitors have been tested in the clinic for NSCLC. Despite the emergence of novel therapeutics and their application in cancer therapy, the overall survival rate of lung cancer patients remains 15%. To develop more effective therapies for lung cancer we have combined the anti-EGFR antibody (Clone 225) as a molecular therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 39 publications
3
100
0
Order By: Relevance
“…The EGFR was found to act as a strong prognostic indicator in head and neck, ovarian, cervical, bladder and oesophageal cancer. 97 The epidermal growth factor receptor (EGFR) is overexpressed in 80% of non-small cell lung cancer (NSCLC), 98 80-100% of human head and neck cancer cells, 14-91% of human breast cancer cells, and 30-50% of human pancreatic cancer cells. 95 Epidermal growth factor receptor (EGFR) is an important anti-cancer therapy target that is applicable to many cancer types.…”
Section: Lipophilic Prodrugsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EGFR was found to act as a strong prognostic indicator in head and neck, ovarian, cervical, bladder and oesophageal cancer. 97 The epidermal growth factor receptor (EGFR) is overexpressed in 80% of non-small cell lung cancer (NSCLC), 98 80-100% of human head and neck cancer cells, 14-91% of human breast cancer cells, and 30-50% of human pancreatic cancer cells. 95 Epidermal growth factor receptor (EGFR) is an important anti-cancer therapy target that is applicable to many cancer types.…”
Section: Lipophilic Prodrugsmentioning
confidence: 99%
“…In vitro uptake and cytotoxicity of EGF-GemC18-NPs realised with different human breast adenocarcinoma cell lines showed a correlation between EGFR density on the cell surface and cell uptake and toxicity. 86,98,100,101 In cell culture, EGF-GemC18-NPs uptake by tumour cells was correlated to the EGFR density, whereas the uptake of untargeted GemC18-NPs …”
Section: Lipophilic Prodrugsmentioning
confidence: 99%
“…There are three major pathways to regulate autophagy initiation: (1) the mammalian target of rapamycin (mTOR) that negatively regulates autophagy; (2) the Beclin 1/VPS34/ Atg14 complex and (3) two ubiquitin-like conjugation processes that generate membrane-bound protein complexes, promoting the formation of LC3-conjugated autophagosome. 20 In our study, we found that inhibition of mTOR by Fe 3 mammalian homologous of yeast Atg6, which plays a key role in the process of autophagy. 21 In intact cells, Beclin 1 forms a complex with Bcl-2; therefore Bcl-2 acts as an inhibitor of autophagy.…”
Section: Discussionmentioning
confidence: 62%
“…1,2 Ferroferric oxide (Fe 3 O 4 ) nanoparticles (NPs) are one such material displaying great potential for medical application; however, recent studies have demonstrated that these NPs might induce apoptosis and other cell responses. 3 It was reported that Fe 3 O 4 NP-induced apoptosis depends on the cell type. As a drug carrier, these NPs display very limited toxicity to cancer cell lines such as cervical cancer cells, but induce cytotoxicity and apoptosis in non-small lung cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation